Unravelling research jargon for the public - Bale, Michael; John, Matthew; Maclean, Nicola (International Journal of Population Data Science, 2025)
Objectives Being open and transparent with the public around research with data is a real challenge, especially given the language typically used. Our aim was to provide an easy tool for both administrators to update, and intuitive for the general public to use. Method The web-based tool that was developed needed to provide answers quickly and easily. To address this issue, members of the public were consulted to compile a list of research terms that needed breaking down. The terms were then categorised into subject areas and given additional taxonomies to allow users to drill-down and filter the terms. Text-based search functionality was added to broadly cover the Term Names and their Definitions. Another function was created to allow users to submit their own words or terms to the tool’s administrators. Results The resulting interactive glossary was very effective in quickly helping members of the public understand unfamiliar terms and demystify aspects of data research. Allowing the public to submit any terms they couldn’t find allowed for continuous feedback and for administrators to keep the tool fresh with new and relevant content. Conclusion This approach could easily be adapted for any research area, and enhance public buy-in. Constant communication with the public was key to really maximising the tool’s utility.